Avoiding the Doldrums: Evaluating the Need for Change in the Offshore Wind Permitting Process - Hokanson, Mitchell (Columbia Journal of Environmental Law, 2019)
Seventeen of the eighteen warmest years in recorded history have occurred since 2001, and temperatures have increased more than a full degree Celsius since the late 1880s. In line with this upward trend in global temperatures, 2017 was the second warmest year in recorded history, and the highest without an El Niño event. Experts agree that much of this change is due to the greenhouse effect—a process in which certain gases, called greenhouse gases (“GHGs”), in Earth’s atmosphere trap energy from the sun, which results in higher temperatures. While some GHGs are naturally part of the atmosphere, human activity has greatly contributed to the current atmospheric stockpile. To avoid the worst of climate change’s effects, some climate scientists have called for a concerted effort to limit global temperature change to 2 degrees Celsius. This 2 degree goal is also found in the Paris Agreement. There is also an appetite to limit the change to 1.5 degrees Celsius, evidenced by the invitation for the Intergovernmental Panel on Climate Change (“IPCC”) to prepare a report on the impacts of a 1.5 degree Celsius warming found in the Decision of the 21st Conference of Parties of the United Nations Framework Convention on Climate Change. The IPCC recently issued a report detailing the possible impacts of a 1.5 degree shift and compares these to the possible impacts of a 2 degree shift. One way to limit climate change is to decarbonize a country’s energy supply. That is, shifting away from burning fossil fuels, like coal and gas, to harnessing renewable sources, like wind and solar, in order to reduce GHG emissions. Organizations such as the Deep Decarbonization Pathways Project (“DDPP”) have recommended several energy-mix scenarios to limit climate change to 2 degrees Celsius by limiting fossil fuel usage and increasing the usage of renewable energy sources. Limiting climate change requires speedy and extensive development of renewables. The DDPP has created several development scenarios that would limit climate change to 2 degrees Celsius, all of which would require a massive increase in the amount of wattage generated by renewable sources. To generate this wattage, many more renewable facilities would need to be constructed in the United States. The DDPP’s High Renewables Scenario calls for a whopping 313,208 megawatts (“MW”) of offshore wind generation by 2050, and even the Mixed Scenario—which envisions a balance of nuclear power, renewables, and natural gas—calls for 186,802 MW of offshore wind generation capacity by 2050. For some context, the Block Island facility, the first and only wind generation facility in the U.S. and discussed in Section II.A, generates only 30 MW. Although haste is necessary given the predictable effects of climate change, we must also consider other aspects of environmental protection, such as the protection of biodiversity. Renewable energy generation facilities will occupy extensive amounts of space on land or at sea and may impact important habitats or species. Laws such as the National Environmental Policy Act (“NEPA”) require federal agencies to analyze the environmental impacts of proposed agency action (including the permitting of facilities) and consider this information when determining whether to allow said action. The procedural requirements of NEPA are necessary to guard against unreasonable impacts to the environment. A balance must be struck, choices need to be made, and someone must make them. This is the unenviable position that the Bureau of Ocean Energy Management (“BOEM”) finds itself in when it comes to offshore wind. BOEM is currently the federal agency with the authority to issue wind leases on the Outer Continental Shelf (“OCS”), and is thus on the horns of a dilemma—balancing its dual mandates of environmental protection and speedy development of energy facilities on the OCS. This Note will evaluate the process that BOEM has developed thus far for making such determinations. Given BOEM’s mixed success in getting wind energy facilities built, the litigation surrounding the Wind Energy Area offshore New York, (“NY WEA” or “Empire Wind”), is of particular importance, as it brings into question the adequacy of BOEM’s leasing procedures. By reviewing the challenges, or lack thereof, to three of BOEM’s currently leased facilities, and reviewing critiques of the leasing process by environmental law scholars, this Note will evaluate whether changes should be made by determining the strengths and weaknesses of BOEM’s current leasing process. Intelligent minds could differ on whether BOEM’s current leasing procedures satisfy their obligations under environmental laws such as NEPA and OCSLA. Although BOEM has prevailed in the recent litigation surrounding Empire Wind, the agency should nevertheless consider retooling its procedures in order to incorporate programmatic environmental impact statements (“EISs”), broadly-scoped studies evaluating the impacts of large-scale proposals or plans. Although slower and more expensive, these programmatic EISs could lay the groundwork for resolving disputes over offshore wind development by showing that wind energy facilities are sited in locations that limit environmental impacts and other harms. BOEM previously issued a programmatic EIS in 2017 looking at the entire OCS and should continue this trend by issuing smaller programmatic EISs focused on particular regions—such as the Gulf Coast or the Mid-Atlantic regions—instead of proceeding in a piecemeal manner. Part I of this Note provides a summary of relevant environmental law and regulations and the current political climate surrounding renewable energy development in the United States. It will focus particularly on NEPA, the Outer Continental Shelf Lands Act (“OCSLA”), BOEM’s Smart from the Start initiative, and BOEM’s current leasing procedures, as they are all under scrutiny in the NY WEA litigation. Part I will also discuss President Trump’s recently issued Infrastructure Plan. Part II of this Note will evaluate whether BOEM’s procedures adequately balance the need for speed in developing alternative energy and environmental protection by looking at three different proposed offshore wind energy projects: Block Island off the coast of Rhode Island, Cape Wind off the coast of Massachusetts, and Empire Wind off the coast of New York. This Note will analyze the lease processes utilized in the former two, and then analyze the legal challenge to BOEM’s recent lease of the NY WEA for the Empire Wind project, Fisheries Survival Fund v. Jewell. Part II will then propose solutions to some of the potential shortcomings of the leasing process. Finally, Part III of this Note will look at potential changes and solutions to the approval process offered by environmental law scholars and evaluate them in light of BOEM’s current process. It will primarily focus on the recommendations made by Professor Michael B. Gerrard in his article Legal Pathways for a Massive Increase in Utility-Scale Renewable Generation Capacity and offer a sympathetic analysis.